Retraction notice to "g-C3N4 nanosheet adorned with Ag3BiO3 as a perovskite: An effective photocatalyst for efficient visible-light photocatalytic processes" [Mater. Sci. Semicond. Process. 125 (2021) 105651]. (February 2022) - Nguyen, Van-Huy; Mousavi, Mitra; Ghasemi, Jahan B.; Van Le, Quyet; Delbari, Seyed Ali; Namini, Abbas Sabahi; Asl, Mehdi Shahedi; Shokouhimehr, Mohammadreza; Jang, Ho Won; Mohammadi, Mohsen
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief as the validity of the results from Figure 3b, c and 5b cannot be guaranteed. The spectral noise from Figure 3b, c appears similar to the noise of spectra from other papers published by the authors: Figure 3b, c of the article published by the Journal of Photochemistry and Photobiology A: Chemistry 406 (2021) 113023 https://doi.org/10.1016/j.jphotochem.2020.113023, Fig. 3b and c of the article published by the Journal of Colloid and Interface Science 587 (2021) 538–549 https://doi.org/10.1016/j.jcis.2020.11.011 and Fig. 5b and c of the article published by Separation and Purification technology article-in-press (2021) 118511 https://doi.org/10.1016/j.seppur.2021.118511 . Also, the graphs from Figure 5b appear similar to graphs from Figure 9c of the article that Soheila Asadzadeh-Khaneghah, Aziz Habibi-Yangjeh and Davod Seifzadeh have previously published in the Journal of the Taiwan Institute of Chemical Engineers 87 (2018) 98–111 https://doi.org/10.1016/j.jtice.2018.03.017, despite the fact that they purportedly described distinct materials. One of the conditions for submitting a paper for publication is that authors declare explicitly that their work is original and has not appeared in any publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.